1997
DOI: 10.1088/0741-3335/39/5/004
|View full text |Cite
|
Sign up to set email alerts
|

Structure of then= 1 mode responsible for relaxation and current drive during sustainment of the SPHEX spheromak

Abstract: The structure of the n = 1 mode in the SPHEX spheromak, which plays a central role in relaxation during sustainment, is investigated by analysing the measured voltage fluctuations in the central plasma column. By combining these results with a suitably defined helical magnetic flux function, the mode is found to be due to a rotating helical distortion of the open linked flux. We propose that the distortion is due to a saturated current-driven kink mode of the open flux tube. The prolongation of this 'helical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
59
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 35 publications
13
59
0
Order By: Relevance
“…Toroidal current is successfully sustained against resistive decay with the n = 1 oscillations. In the current drive phase, a helical distortion of a central open flux column, rotating toroidally, which is in good agreement with SPHEX observations [4], can be observed. We found that an asymmetric plasmoid is generated by the distortion on the gun side, and that the current is periodically fed from it, as shown in Fig.…”
supporting
confidence: 87%
“…Toroidal current is successfully sustained against resistive decay with the n = 1 oscillations. In the current drive phase, a helical distortion of a central open flux column, rotating toroidally, which is in good agreement with SPHEX observations [4], can be observed. We found that an asymmetric plasmoid is generated by the distortion on the gun side, and that the current is periodically fed from it, as shown in Fig.…”
supporting
confidence: 87%
“…Helically distorted structures also are found in numerical simulations (e.g. Gerrard et al 2001) and are observed in experiment (Duck et al 1997). The minimum energy state is the cylindrical Bessel function field if αR < 3.11 but if the normalised helicity exceeds some critical value, then the field with lowest energy has the fixed value αR ≈ 3.11 and is a combination of the axisymmetric and first helical modes…”
Section: Calculation Of Energy Releasementioning
confidence: 54%
“…This is not the first reporting of cross-field current in supposedly force-free spheromaks. The SPHEX group reported that up 50 % of the gun current went into the outer wall but only 10% of the gun flux diffused into it 5 is predominantly parallel to the wall, i.e. current perpendicular to surfaces is negligible.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…The toroidal angle is φ and ω is referred to as 'the n=1 frequency'. The Spheromak Experiment (SPHEX) 5,6 made internal floating potential, magnetic probe, and Rogowksi (current) probe measurements all the way to the symmetry axis of the equatorial plane of a spheromak while this "n=1 mode" was active. The n=1 mode was the n=1 mode dominates the spheromak during sustainement, and is believed to be responsible for relaxation current drive.…”
Section: Introductionmentioning
confidence: 99%